2008
DOI: 10.1016/j.apcatb.2008.05.020
|View full text |Cite
|
Sign up to set email alerts
|

H2S photodegradation by TiO2/M-MCM-41 (M=Cr or Ce): Deactivation and by-product generation under UV-A and visible light

Abstract: M-MCM-41 molecular sieves (M = Ce or Cr) were prepared by a hydrothermal method and impregnated with TiO 2 . The materials were characterized by XRD, N 2 adsorption-desorption, DRS and XPS. Their potential application to photooxidize H 2 S in a wet gas stream was tested in a continuous flow reactor operating at a flow rate of 110 mL·min -1 at 50% relative humidity and using 30 ppm v of the pollutant. The photocatalytic efficiency using UV-A and visible-light was compared to the activity of TiO 2 /MCM-41 withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Therefore, the photocatalytic reactor in this study had less effect on the removal of H 2 S than that of other organic sulphur compounds. However, several studies have found that H 2 S can be removed efficiently in photocatalytic reactors [52][53][54][55][56][57]. When comparing the experimental setups, several possible reasons for this could be proposed.…”
Section: Initial Concentration Dependencementioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, the photocatalytic reactor in this study had less effect on the removal of H 2 S than that of other organic sulphur compounds. However, several studies have found that H 2 S can be removed efficiently in photocatalytic reactors [52][53][54][55][56][57]. When comparing the experimental setups, several possible reasons for this could be proposed.…”
Section: Initial Concentration Dependencementioning
confidence: 94%
“…In this study, powdered TiO 2 (anatase) was coated on the surface of the TiO 2 filter. However, other researchers have used sol-gel TiO 2 , TiO 2 /M-MCM-41 (M = Cr, Ce), hybrid TiO 2 -SiM g O x or TiO 2 doping with WO 3 [52][53][54][55][56][57]. Lastly, the amount of TiO 2 coated on the ceramic filter may not be sufficient to obtain a sufficiently high density of active sites to adsorb and degrade H 2 S [52].…”
Section: Initial Concentration Dependencementioning
confidence: 95%
“…The TiO 2 photocatalyst modified with noble metal Cu or Ag displayed increased photocatalytic activity for removing hazardous H 2 S. Moreover, Raquel et al. have synthesized TiO 2 /M‐MCM‐41 (M=Cr) successfully, which can effectively photooxidize H 2 S in contrast to Degussa P‐25 TiO 2 . However, the poor adsorption ability and low surface area of TiO 2 still limit its photocatalytic H 2 S decomposition rate .…”
Section: Introductionmentioning
confidence: 99%
“…The CNF/TiO 2 nanowire (CTW) membranes possess a high surface area and a versatile step‐by‐step strategy was used to synthesize the MOF shell on the CTWM membranes. Compared with previous reports about H 2 S degradation, the CTWM membranes have some advantages: 1) a simple step‐by‐step self‐assembly strategy was used to synthesize the MOF shell on TiO 2 nanowires, which can enhance H 2 S adsorption capacity and avoids using expensive noble metals to modify. 2) The CTWM membrane had a larger surface area and allowed the simultaneous adsorption and catalysis of H 2 S. 3) Using CNFs as a catalyst carrier can be helpful for the efficient electron transfer and convenient recovery and recycling characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…3) H 2 S cannot be efficiently removed in the photocatalytic reactor with only TiO 2 (Paper III) [111], and TiO 2 has to be modified by doping other types of photocatalyst or metals on TiO 2 [115][116][117].…”
Section: Figure 1 Advanced Oxidation Processes (Aops)mentioning
confidence: 99%